2015
DOI: 10.1118/1.4930249
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the onboard imaging unit for the first clinical magnetic resonance image guided radiation therapy system

Abstract: The onboard imaging unit of the first commercial MR-IGRT system meets ACR, NEMA, and vendor specifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
54
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 8 publications
4
54
1
Order By: Relevance
“…However, in order to obtain sufficient SNR, the density of 19 F needs to be increased on the molecular basis which is accomplished through perfluorination in which all 1 H atoms in a hydrocarbon chain are replaced with 19 F atoms. 64,69 These perfluorocarbons (PFCs) are similar to common organic compounds in their molecular structure except that they are very electronegative.…”
Section: Biomarkers and Mrimentioning
confidence: 99%
See 4 more Smart Citations
“…However, in order to obtain sufficient SNR, the density of 19 F needs to be increased on the molecular basis which is accomplished through perfluorination in which all 1 H atoms in a hydrocarbon chain are replaced with 19 F atoms. 64,69 These perfluorocarbons (PFCs) are similar to common organic compounds in their molecular structure except that they are very electronegative.…”
Section: Biomarkers and Mrimentioning
confidence: 99%
“…Since then other sites have followed suit with clinically treating with their VRS such as the University of California, Los Angeles (Los Angeles, CA). 22 Hu et al 19 evaluated the VRS' image quality as compared with the American College of Radiology's guidelines for the Washington University VRS and found that the system met all American College of Radiology and vendor specifications. Hu et al 19 measured slice position error to be ,1 mm, slice thickness error was ,0.5 mm and the resolved high-contrast spatial resolution was 0.9 mm.…”
mentioning
confidence: 99%
See 3 more Smart Citations